PENGEMBANGAN BAHAN AJAR TEKS SURAT BERDASARKAN SURAT PRIBADI DAN SURAT DINAS DAN IMPLEMENTASINYA DALAM PEMBELAJARAN DI SMP - Panji Setyo Wiguno; Jaja Jaja (Program Studi Pendidikan Bahasa Indonesia Pascasarjana UGJ, 2019)
This study aims to develop teaching materials for letter texts based on personal letters and letters from agencies in Brebes Regency. This research was carried out because there were still limited effective letter text textbooks that were developed and used in learning for VII graders in junior high school. The purpose of this research is to produce teaching material designs, obtain information about the feasibility of textbooks, and the effectiveness of the use of teaching materials in class VII SMP, and produce the final product of textbooks. To achieve this goal, the Research and Development (R&D) research method is used by using the ADDIE research model. Based on the results of the research that has been carried out it can be seen that the textbooks developed are very feasible and can be effectively used in learning for VII grade students in junior high schools.